Bringing Quality and Service Management to Start-Ups: Implementing a Framework for Service Development - Segertoft, Axel; Örtorp, Johan (My University, 2025)
The thesis focuses on developing a structured service development model tailored for a Swedish start-up (referred to as The Company) that supports non-profit sports organizations. The core aim is to help these organizations operate more efficiently and sustainably by offering services that reduce operational costs and increase revenue. The study explores three main research questions, focusing first on assessing the current service development of the company; second, on identifying the actors involved in value creation; and third, on how a model for new service development (NSD) can be tailored and designed to support the needs of sport organizations. The study integrates theories on value co-creation theory, service creation and use of new service development models, and applies them to the context of sport organizations. It includes empirical data from interviews with various stakeholders (club managers, volunteers, members, and sponsors) and results in actionable insights and managerial implications for implementing the proposed conceptual NSD framework. The conceptual NSD framework focus on structured feedback loops and club segmentation, ensuring services are adapted to varying needs of amateur, semi-elite and elite sport organizations. The study showed that in the context of sport organizations, value co-creation and new service development requires engaging volunteers, members, and partners by relations building and focusing continuous feedback.
Keywords: Service Development, Value Co-Creation, Start-Ups, Sport Organizations, New Service Development (NSD), Volunteers Engagement, Customer Feedback, Non-Profit Management, Quality Management